Impact of Fiscal Policy on Economic Growth in Developing Countries - Arjang Arjang; Hendri Khuan; Rudy Badrudin; Loso Judijanto; Ummy Kalsum; Rizal Ruben Manullang (PT. Anagata Sembagi Education, 2025)
This study examines the impact of fiscal policy on economic growth in developing countries, emphasizing the role of government expenditures and tax policies in shaping economic outcomes. The findings indicate a strong positive relationship between fiscal policy and economic growth, where government spending and tax measures significantly contribute to enhancing economic performance. Specifically, the study reveals that well-structured fiscal policies can effectively promote growth, with key fiscal tools such as public investment and tax reforms playing a vital role. The results suggest that developing countries can achieve higher economic growth by implementing strategic fiscal measures, which can address structural challenges and encourage sustainable development. The research provides essential insights for policymakers to design more efficient fiscal policies that foster long-term economic stability and growth.